2020
DOI: 10.1093/cdn/nzaa053_091
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology Integrated into a Large-Scale Nutrition Program Enables Age-Appropriate Home Visits and Counseling for Mothers of Infants in India

Abstract: Objectives An mHealth job aid and real time monitoring tool currently targets over 1 million community health workers in India (Anganwadi workers – AWWs). Previous studies have shown that mHealth interventions can be effective at a small scale. In this study, we evaluate whether this at-scale mHealth intervention improved the quantity and quality of AWW home visits and counseling. We also examined whether these improvements led to better infant and young child feeding (IYCF) practices among b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Additionally, our review did not find any studies which incorporated the use of mobile health (mHealth) as part of an intervention package for improving IYCF. 105 Future experimental studies that consider the use of mHealth techniques are required, especially that previously published studies have shown the positive impacts of interventions (in the form of voice messages, SMS and phone calls) on IYCF practices. [106][107][108] Finally, interventional studies that consider the role of fathers/partners as well as grandmothers in improving IYCF behaviours may be warranted in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our review did not find any studies which incorporated the use of mobile health (mHealth) as part of an intervention package for improving IYCF. 105 Future experimental studies that consider the use of mHealth techniques are required, especially that previously published studies have shown the positive impacts of interventions (in the form of voice messages, SMS and phone calls) on IYCF practices. [106][107][108] Finally, interventional studies that consider the role of fathers/partners as well as grandmothers in improving IYCF behaviours may be warranted in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our review did not nd any studies which incorporated the use of mobile health (mHealth) as part of an intervention package for improving IYCF [72]. Future experimental studies that consider the use of mHealth techniques are required, especially that previously published studies have shown the positive impacts of interventions (in form of voice messages, SMS, and phone calls) on IYCF practices [73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…ICDS-CAS was thus envisaged to reduce this burden. Recent evaluations have also shown that mHealth interventions such as ICDS-CAS can support gains in immediate term service delivery outcomes by enabling more age-appropriate home-visits and counseling but require longer term evaluations to improve other outcomes ( 20 ).…”
Section: Introductionmentioning
confidence: 99%